BEYOND THE AKHARA: GENDERED SPACE AND WOMEN’S AGENCY IN INDIAN SPORTS FILMS - Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The cinematic realm, reflecting society's evolving ethos, has increasingly become a platform for exploring gender dynamics, particularly in sports films. In the Indian context, sports cinema transcends mere athletic narratives to interrogate entrenched societal norms, providing a fertile ground for reimagining gendered spaces. This manuscript delves into the transformative portrayal of women in Indian sports films, focusing on how these narratives carve out spaces of empowerment within a historically patriarchal framework. From akhara (mud–pit) to international arenas, sports films have spotlighted the indomitable spirit of women who defy cultural constraints to assert agency. This essay will study two films, Dangal (2016) and Saand Kii Aankh (2019), chronicling female sportsperson’s journey but foregrounding their confrontation with regressive traditions that relegate women to the domestic sphere. These cinematic portrayals challenge the deeply ingrained dichotomies of strength versus femininity, public versus private spaces, and tradition versus progress. By employing powerful visual storytelling and evocative character arcs, Indian sports films serve as a cultural critique of spatial inequalities, offering narratives where women reclaim the akhara—both literal and symbolic—as arenas of identity and empowerment. The synergy of athleticism and cinematic representation redefines femininity, presenting women not as objects of aesthetic idealization but as agents of resilience and defiance. This paper examines the intersection of gender, space, and agency in sports films, arguing that these narratives do more than entertain—they disrupt normative constructs, fostering dialogue on women’s rights and their rightful place in public life. Ultimately, the paper posits that Indian sports cinema, in its nuanced portrayal of gendered spaces, catalyses a broader discourse on societal transformation and women's emancipation.